The synthesis of branched sugars and iminosugars - Parry, LL (2011)
Iminosugars, carbohydrate analogues in which nitrogen replaces the endocyclic oxygen, have attracted much interest due to their biological activity. Iminosugars inhibit carbohydrate-processing enzymes, thereby affecting many biological processes. Several iminosugars are licensed drugs, with many more compounds undergoing clinical trials. The main subject of this thesis is the synthesis and evaluation of novel iminosugars, particularly the effects of structural modifications on the biological activity of these compounds. Chapter 1 describes the role of carbohydrate-processing enzymes in the body, and explores the therapeutic applications of iminosugars that arise from their activity against these enzymes. Examples of substituted iminosugars are reviewed, and the effects of substituents on enzyme inhibition are described. Chapter 2 concerns methyl-branched swainsonine derivatives. Swainsonine has shown potential as a cancer treatment through its inhibition of α-mannosidase. The synthesis of (6R)- and (6S)-C-methyl D-swainsonine is described; both compounds were potent and selective α-mannosidase inhibitors (IC50 3.8 μM, 14 μM). Although less active than the parent compound, their selectivity for Golgi mannosidase over lysosomal mannosidase may be more important than the absolute value against the model enzyme. Chapter 3 describes the synthesis of a 2-C-methyl L-fucose derivative. A diastereoselective Kiliani reaction allowed the formation of a single lactone bearing a new quaternary centre. The utility of this intermediate in accessing di-branched iminosugars was explored; however, attempts to introduce nitrogen to the lactone lacked the necessary stereoselectivity. Chapter 4 relates to the synthesis of pyrrolidine iminosugars, specifically methyl amides. Two enantiomeric dihydroxyproline amides were synthesised; the D-proline derivative was a potent β-N-acetylhexosaminidase inhibitor (IC50 values of up to 3.6 μM), but the L-enantiomer was completely inactive. Inhibition of N-acetylhexosaminidases is relevant to the treatment of cancer and lysosomal storage diseases, and this work contributed to a wider project investigating the effects of altered stereochemistry on the biological activity of pyrrolidine amides.